Saberes e sabores da docência : o que move o professor de biologia na/para a sala de aula - Confortin, Renata (2014)
This study is circumscribed on the epistemology of practice field and is justified by the need to understand the processes of professional formation and appropriation and mobilization of teachers knowledge, in order to understand the practices that take place in daily life of schools and classroom. In the effort to identify the specificities that characterize the practice of two Biology teachers in High School, that stand out by the quality of their professional performances, it was investigated how it is constituted their teachers knowledge at the confluence of family, school, educational and social experiences. Still, it was seek to understand what knowledge they mobilize to perform his/her job of teaching Biology (well), related of the experience put in practice, the class management, the subject management and the will of being a teacher. Based on studies by Tardif (2000, 2012), Gauthier et al. (1998), Nóvoa (1995a, 1995b, 2007), Pimenta (2012), Perrenoud (2001, 2002, 2013), among others, to attain these purposes, the methodological path was traversed from the triangulation of three techniques: the life story, the semi structured interview and the classes observation. The preliminary results indicate processes that configure singularities in certain moments and in others regularities in both constitution and form of knowledge mobilization by teachers. It is understood, as the centrality of these pathways the teachers influence throughout elementary and higher education - especially to the learnings that relate to interpersonal values, such as respect, affection, humanization of pedagogical relationships - and the central place of experience on the constitution of teacher knowledge. Concerning to the modes of knowledge mobilization, it is understood that the paths are very individualized in function, among other factors that appeared less evident, of the stage that the teacher is in his/her career. The experienced teacher seems to mobilize knowledge more specifically in the class management, on opposite, the novice teacher does it in the subject management field. Still, it is evident that the detached practice of two teachers subject of this investigation is marked by the will of teaching, a deep caring for students, the importance of being a teacher, with the responsibility that they assume the conduct the classroom